Pilgrimage Tourism Dynamics in Rural Nepal: Assessment of Growth Prospects and its Challenges in Haleshi - Dhakal, Bhola Nath (The Third Pole: Journal of Geography Education, 2024)
Tourism has unavoidable perspective worldwide. It is a multi-dimensional societal, cultural and economic activity that involves movements of people from one place to another place particularly out of their usual environment with the aim of getting knowledge on new place, cultures, religions, traditions and so on. Pilgrimage tourism is a specific type of tourism that involves travelling to the holy or sacred places for religious and spiritual purposes in different places around the World. This study aims at exploring opportunities and challenges of pilgrimage tourism in Haleshi area of Khotang district. Household questionnaire survey, focus group discussion, Key informant interview and field observation, interactions with tourists/pilgrims have been adopted as primary sources of data and published research articles, census data and government documents have been used as secondary data to accomplish this study. This study reveals that there are many opportunities like natural cave and beautiful sceneries, unique traditions and cultures, religious harmony among different religious group etc. for the development of pilgrimage tourism in the study area however, many challenges like poor infrastructures (road, communication, markets, hotels and accommodations), quality food, security services, public awareness, advertisement and publicity, safe water and sanitation are the notable problems faced by the pilgrimage tourists as well as local communities in the study area.